2015
DOI: 10.4238/2015.october.29.37
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expression analysis of four HD-ZIP III family genes targeted by microRNA166 in peach

R J3
et al.

Abstract: ABSTRACT. MicroRNA166 (miR166) is known to have highly conserved targets that encode proteins of the class III homeodomain-leucine zipper (HD-ZIP III) family, in a broad range of plant species. To further understand the relationship between HD-ZIP III genes and miR166, four HD-ZIP III family genes (PpHB14, PpHB15, PpHB8, and PpREV) were isolated from peach (Prunus persica) tissue and characterized. Spatio-temporal expression profiles of the genes were analyzed. Genes of the peach HD-ZIP III family were predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In Arabidopsis thaliana, the HD-ZIP III family includes five genes, ATHB8, ATHB15, phavoluta (PHV), phabulosa (PHB), and revoluta (REV), which determine and direct the differentiation and maintenance of stem apex meristem cells, the apical meristem, vascular bundle development, and organ polarity [8,9]. An analysis of the expression of the HD-ZIP III genes PpHB14, PpHB15, PpHB8, and PpREV in peach (Prunus persica) tissue revealed that they are regulated by miR166 during fruit development [10]. As plant-specific transcription factors (TFs), the HD-ZIP III TFs regulate plant development and auxin-related gene expression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, the HD-ZIP III family includes five genes, ATHB8, ATHB15, phavoluta (PHV), phabulosa (PHB), and revoluta (REV), which determine and direct the differentiation and maintenance of stem apex meristem cells, the apical meristem, vascular bundle development, and organ polarity [8,9]. An analysis of the expression of the HD-ZIP III genes PpHB14, PpHB15, PpHB8, and PpREV in peach (Prunus persica) tissue revealed that they are regulated by miR166 during fruit development [10]. As plant-specific transcription factors (TFs), the HD-ZIP III TFs regulate plant development and auxin-related gene expression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are 21 miR166s in soybean, 17 in Populus trichocarpa , 9 in Arabidopsis thaliana , 13 in maize, rice, and Physcomitrella patens according to miRBase database (Release 21, June 2014). The miR166s in multigene family were found to be highly conserved to target HD-ZIP III family genes such as REVOLUTA ( REV ), PHABULOSA ( PHB ), PHAVOLUTA ( PHV ), CORONA ( CNA ) and ATHB8 in a broad range of plant species, indicating that they might exhibit high degree of functional redundancy [ 20 23 ]. Nevertheless, emerging evidences indicate that functional specialization exists in miR166 family.…”
Section: Introductionmentioning
confidence: 99%
“…reported that miR165/166 showed the powerful functions in modulating auxin signaling and stress responses in Arabidopsis 16 , and displayed severe defects in the vegetative and reproductive stage. Members of the HD-Zip ( homeodomain-leucine zipper ) and Hox9 were the target genes of miR166, and the HD-Zip has been shown to regulate leaf shape development in Arabidopsis 35 , while Hox9 was found to play a role in wheat grain development 7 . Here, transgenic STTM165/166 plants showed significantly reduced seed number and sterile siliques in Arabidopsis, suggesting that miR166 plays vital roles in grain development and might be a useful evidence to improve inferior grain size in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…VPE1 was found to be required for efficient glutelin processing in rice 37 , while ARF played a vital role in the IAA pathway in plant development 38 . As a member of the HD-ZIP family, the PHB gene was shown to mainly regulate leaf shape development and responses to abiotic stresses in Arabidopsis 16 , 35 . LEA gene, which is regulated by miR164 and miR1892, plays a key role in embryogenesis development and resistance to stress 39 .…”
Section: Discussionmentioning
confidence: 99%